Development of banana chips: Analysis of nutritional and sensory characteristics of banana chips as influenced by frying conditions - Mesfin Wolde Deboch,; Abadi Gebre Mezgebe, (International Journal of Agricultural Research, Innovation and Technology, 2024)
Banana (Musa sapientum L) is a widely grown and consumed fruit due to its distinct aroma and taste. In Ethiopia, there is a lack of knowledge and trends on the processing and consumption of processed and shelf-stable banana products. The aim of this study was to evaluate the effects of frying time and layering of Moringa stenopetala leaf powder on the proximate composition, oxidative stability and sensory properties of green banana chips. In this study, prepared chips from green bananas using two levels of Moringa stenopetala leaf powder layers (3% & 6%) and three levels of frying time (1.5, 2.0, & 2.5 minutes) following standard methods. Proximate Composition, Oxidative Stability and Sensory Properties of the chips were analyzed. The results showed that the banana chips had moisture (3.35–7.34%), total ash (5.67–13.65%), crude ﬁber (4.43–12.43%), crude fat (3.34–11.70%), crude protein (3.56-13.80%), carbohydrate (57.78–67.29%). Descriptive sensory analysis (DSA) showed that banana chips prepared with layering of M. stenopetala leaf powder was bitter, darker, rougher, and more astringent than chips fried from only banana. Banana chips fried without Moringa leaf powder for 2.5 minutes were crispier. M. stenopetala leaf powder layered banana chips were lower in quality and had weak acceptability compared with banana chips fried without M. stenopetala leaf powder. This study suggested that layering M. stenopetala leaf powder during prolonged frying to banana chips improves nutritional value and oxidative stabilities without compromising the sensory properties of banana chips. Int. J. Agril. Res. Innov. Tech. 13(2): 1-5, Dec 2023